2011
DOI: 10.1016/j.bbamem.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between membrane permeability and specificity of human secretory phospholipase A2 isoforms during cell death

Abstract: Summary During apoptosis, a number of physical changes occur in the cell membrane including a gradual increase in permeability to vital stains such as propidium iodide. This study explored the possibility that one consequence of membrane changes concurrent with early modest permeability is vulnerability to degradation by secretory phospholipase A2 (sPLA2). The activity of this hydrolytic enzyme toward mammalian cells depends on the health of the cell; healthy cells are resistant, but they become susceptible ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 69 publications
4
25
0
Order By: Relevance
“…Consequently, the membrane permeability of propidium iodide does not greatly increase in NnaPLA 2 -and notexin-induced apoptosis of K562, U937 and SK-N-SH cells (Liu et al, 2009;Chen et al, 2010a,b). Nelson et al (2011Nelson et al ( , 2012 also found that A. piscivorus piscivorus PLA 2 did not cause the membrane of ionomycin-and thapsigargin-treated cells to become free permeable for propidium iodide.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Consequently, the membrane permeability of propidium iodide does not greatly increase in NnaPLA 2 -and notexin-induced apoptosis of K562, U937 and SK-N-SH cells (Liu et al, 2009;Chen et al, 2010a,b). Nelson et al (2011Nelson et al ( , 2012 also found that A. piscivorus piscivorus PLA 2 did not cause the membrane of ionomycin-and thapsigargin-treated cells to become free permeable for propidium iodide.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies suggested that membrane structure contributed to the level of membrane susceptibility to A. piscivorus piscivorus PLA 2 in addition to PS externalization (Bailey et al, 2007(Bailey et al, , 2009Nelson et al, 2011Nelson et al, , 2012. Nevertheless, the effect of membrane-interacted mode of PLA 2 enzymes and membrane compositions on PLA 2 activity does not explore in the studies of Bailey et al (2007Bailey et al ( , 2009 and Nelson et al (2011and Nelson et al ( , 2012. Nelson et al (2011) found that A. piscivorus piscivorus PLA 2 showed different activity on hydrolyzing the membrane of ionomycin-, dexamethasone-or thapsigargin-treated cells.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations